KUSU BUE SEBAGAI RITUS PERALIHAN REMAJA PUTRI WOE TIPO DI DESA NARUWOLO, KECAMATAN JEREBU’U, KABUPATEN NGADA NUSA TENGGARA TIMUR - Fengi, Anastasia Chrisanta Alwinda; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
The Kusu Bue Rite is a cultural initiation ceremony or maturation process women before marriage. Women will be secluded or ruki inside small house called sao are. This study uses the theory of the rite of passage and the inauguration ceremony by Van Gennep (1987). Qualitative research data obtained with ethnographic research models, participants, observations, interviews, literature studies, and data analysis in order to processing field findings. The process of the kusu bue rite lasts for eight days and seven nights. The results of this study also found meaning in the implementation of Kusu bue rites against marriage. The Kusu Bue Rite inherits meanings which is beneficial for marriage in the typo tribal community in Naruwolo village namely the meaning of holiness, the meaning of education, the meaning of social, the meaning of morality, and Meaning of Unity and Unity.